The Role of Papuan Women in Isinga and Namaku Teweraut - Kurniatama, Arief; Y. Slamet, Suyitno, St. (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: The role initiated by Papuan women in providing balance and survival can in fact be realized by caring for others. This study aims at describing the role of Papuan women in Isinga and Namaku Teweraut. This research method uses content analysis with a feminist literary approach. The data is obtained using literature and interviews. The results of this study indicate that by managing the potential in women it will be able to anchor the nation's rank, improve the fulfillment of the needs and quality of life, give a positive influence on survival, and women have a big contribution in creating peace.